Eksplorasi Budaya “Bapa’ Babu’ Guru Rato” dalam Menciptakan Kebersyukuran Siswa kepada Orang Tua - Azizatul Karimah; Mohammad Mahpur; Yulia Solichatun (Faculty of Psychology, Sunan Gunung Djati Islamic State University of Bandung, 2022)
Gratitude is one of the concepts in Positive Psychology, which is the field of psychology that views life from a positive perspective. The cultural heritage of